Profitable relationships with key customers: how suppliers manage pricing and customer risk - Ryals, Lynette (Taylor & Francis, 2006)
Increasingly, the measurement and management of customer profitability and customer lifetime value are recognized as important elements in marketing's contribution to shareholder value. In recent years numerous papers have been written about the value of customers, mostly case study based and confined to analysis of single companies or industries. This article reports on research that takes a wider perspective and examines how best-practice companies across a range of different industries try to manage their relationships with key customers profitably. The contribution of this research is to show how best- practice companies manage pricing, costs to serve, and customer risk in their key account portfolios.
Keywords: Customer lifetime value; customer portfolio; key account management; pricing; customer risk